Who seeks help in a crisis? Temporal analysis of anti-trafficking helpline contacts over the pandemic - Lisa Tompson; Ella Cockbain (BMC Public Health)
Abstract Background Human trafficking and extreme exploitation ("modern slavery") violate fundamental human rights and cause severe harm to individuals' well-being. Anti-trafficking helplines provide critical support for victims/survivors, yet little research has explored their usage patterns, particularly during crises. This study examines how the Covid-19 pandemic influenced reporting to the UK’s Modern Slavery & Exploitation Helpline, aiming to identify trends in help-seeking behaviour during this period of significant social disruption. Methods This study analysed 8,386 cases from the Helpline between October 2016 and December 2021. We took a descriptive approach, as assumptions for causal analyses could not be met. We used seasonal decomposition methods to separate underlying trends over the pandemic from seasonal effects, focusing on caller proximity and exploitation sub-types. Results Helpline contacts decreased following the introduction of Covid-19 restrictions, although case volume remained steady compared to pre-pandemic levels. Reporting patterns shifted: reports of criminal and sexual exploitation increased, while those of labour exploitation declined. Self-reports from victims/survivors rose notably during in-person work restrictions, particularly for labour exploitation in essential industries. Reports from the public about suspicious activity dropped and did not rebound post-lockdown, suggesting long-term changes in public reporting behaviour. Conclusions The study demonstrates how the Covid-19 pandemic affected reporting to a major anti-trafficking helpline, revealing increased self-reports from victim/survivors but a decline in community-based reporting. These findings highlight the importance of helplines as a public health intervention during crises and underscore the need for enhanced support infrastructure during periods of social and economic disruption. Future research should investigate the underlying causes of these shifts in reporting and explore ways to improve service access for victim/survivors of trafficking during emergencies.